Study on anti-frost heave effect of new thermal insulation subgrade of highway in seasonally frozen soil regions. - Xiaoqiang Mi; Wenqiang Zhang; Ge Zhang; Xinbin Wang (PLoS ONE)
Frost heave is one of the important factors affecting the long-term stability and safe operation of subgrade in seasonally frozen soil regions. To investigate the anti-frost heave effect of foam concrete insulation and composite insulation structure subgrade, a multi-physics fields coupling numerical simulation was employed. From the perspective of hydrothermal process of the subgrade, the ground temperature distribution, maximum freezing depth, ice distribution, and maximum frost heave are systematically analyzed. The results indicate that the foamed concrete insulation layer subgrade exhibits a significant anti-frost heave effect. Meanwhile, to alleviate the sunny-shady slopes effect on subgrade in the seasonally frozen soils regions, the composite insulation structure combining XPS insulation board with foamed concrete insulation was recommended. Moreover, the appropriate anti-frost heave measures for subgrade are proposed, which considering the different frost heave characteristics. The findings can serve as a reference for the prevention and control of frost heave in highway subgrade and for the application of foam concrete insulation layers in seasonal frozen soil regions.